2020
DOI: 10.1038/s41598-020-67835-4
|View full text |Cite
|
Sign up to set email alerts
|

Wireless monitoring and real-time adaptive predictive indicator of deterioration

Abstract: to assist in the early warning of deterioration in hospitalised children we studied the feasibility of collecting continuous wireless physiological data using Lifetouch (ecG-derived heart and respiratory rate) and WristOx2 (pulse-oximetry and derived pulse rate) sensors. We compared our bedside paediatric early warning (peW) score and a machine learning automated approach: a Real-time Adaptive Predictive Indicator of Deterioration (RAPID) to identify children experiencing significant clinical deterioration. 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Our study agrees with previous studies using wearable devices in that significant amounts of signal loss occurred. 7 Reasons for this may be both physical (eg, poor quality or faulty devices) and contextual. Our rationale in performing this study in patients with tetanus was that they present many issues for wearable devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study agrees with previous studies using wearable devices in that significant amounts of signal loss occurred. 7 Reasons for this may be both physical (eg, poor quality or faulty devices) and contextual. Our rationale in performing this study in patients with tetanus was that they present many issues for wearable devices.…”
Section: Discussionmentioning
confidence: 99%
“…4 Some of these devices have the additional advantage of being able to record continuous data, which allow more complex analysis and may facilitate even better risk prediction. [5][6][7] There is, however, limited use of these devices in the unique and challenging environments of LMIC intensive care units (ICUs). 3 The majority of validatory data concerning wearables come from community settings in relatively healthy ambulatory individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Four studies appeared to meet the inclusion criteria but were excluded at full-text review: two studies were excluded for not reporting a subset of their analysis for the patients using the AMS [32,33]; one was excluded after con rming with the author that the device was not ambulatory at the time of the study [34], and another did not have a comparator group [35]. A total of 4433 patients were included in these studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…In addition, a recent study in the paediatric population concluded that wireless monitoring is feasible and can identify more deteriorations. The authors suggest that by using this in combination with a paediatrics early warning (PEW), some life-threatening events may be prevented [35].…”
Section: Exploratory Outcomesmentioning
confidence: 99%